College Accounting - Chapters 1-32 - Ellis Price John (Mc Graw Hill, 2007)
This 15-hour set contains a discussion of that nature of a erchandising business organized as a sole proprietorship, a narrative of transactions, and specific instructions for end-of-month and end-of-year procedures, and all the forms and working papers needed to complete the practice set. --This text refers to an out of print or unavailable edition of this title.